Does Formality Improve Micro-firm Performance? Evidence from the Brazilian SIMPLES Program - Fajnzylber, Pablo; Maloney, William F.; Montes-Rojas, Gabriel V. (2012)
This paper exploits an extensive Brazilian micro-enterprise survey and the 1996 introduction of a business tax reduction and simplification scheme (SIMPLES) to examine three questions. First, do high tax rates and complex tax regulations really constitute a barrier to the formalization of micro-firms? Second, does formalization improve firm performance measured along several dimensions, including revenues, employment and capital stock? Third, what are the channels through which this occurs? We find that SIMPLES led to a significant increase in formality in several dimensions. Moreover, newly created firms that opt for operating formally show higher levels of revenue and profits, employ more workers and are more capital intensive (only for those firms that have employees). The channel through which this occurs is not access to credit or contracts with larger firms. Rather, it appears that the lower cost of contracting labor leads to adopting production techniques that involve a permanent location and a larger paid labor force.